PENGARUH LATIHAN BOX JUMP TERHADAP DAYA LEDAK OTOT TUNGKAI PADA TIM SEPAK BOLA SUNGAI PAKNING SOCCER CLUB (SSC) SUNGAI PAKNING - ', Imansyah; ', Slamet; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract. This research is conducted to find out there is an influence box jump exercise toward legmusclesexplosivepower in footballplayer team of soccer club (SSC) Sungai Pakning. The weakness has been found out in playing football particularly when heading the ball because jump and the Leg Muscles Explosive Power less of maximal weather in match or exercise. This type of this research wasexperimental and the population was active Football Player team of Soccer club (SSC) Sungai Pakning that consists of 16 players. Data collection technique used istestmethod,that is pre-test and post test. In this research, the sample was measured by Leg Muscles Explosive Power using Vertical Power Jump Test as pre-test. After that, Football Player team of Soccer club (SSC) Sungai Pakning was given a treatment in Box Jump. Next, as the last step to measure the legmusclesexplosivepower as post test to get the result of box jump exercise.The instrument of this research tested the Leg Muscles Explosive Power used vertical Power Jump Test, the functionof this tool is to measure the Leg Muscles Explosive Power. After that, the data was statistic processed, to test to the normality used lilifors test in the significant level 0,05α. Hypothesisthat has been proposed, there was an influence of box jump exercise toward legmuscle explosivepower based on the analysis T test obtained Tcount in amount 3,47 and Ttable 1,75, it means Tcount>Ttable. Regarding to the statistic analysis, pre-test got the result around 0,0815 and the average of post test was 0,0974, so the data was normal. In conclusion, there was an influence box jump exercise toward leg muscles explosive power in football player team of soccer club (SSC) Sungai Pakning.Keywords: Box Jump, Leg Muscles Explosive Power